2020
DOI: 10.1186/s13634-020-00704-4
|View full text |Cite
|
Sign up to set email alerts
|

Consistent independent low-rank matrix analysis for determined blind source separation

Abstract: Independent low-rank matrix analysis (ILRMA) is the state-of-the-art algorithm for blind source separation (BSS) in the determined situation (the number of microphones is greater than or equal to that of source signals). ILRMA achieves a great separation performance by modeling the power spectrograms of the source signals via the nonnegative matrix factorization (NMF). Such a highly developed source model can solve the permutation problem of the frequency-domain BSS to a large extent, which is the reason for t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…In the case study, the recordings from the Huawei Mate30Pro have two channels, so we test the effectiveness of BSS on these recordings. We test five BSS algorithms: AuxIVA [55], ConsistentILRMA [56], FastMNMF [57], LaplaceFDICA [58], and t-ILRMA [59]. The results are shown in Table 28(bottom).…”
Section: Case Study: a Common Officementioning
confidence: 99%
“…In the case study, the recordings from the Huawei Mate30Pro have two channels, so we test the effectiveness of BSS on these recordings. We test five BSS algorithms: AuxIVA [55], ConsistentILRMA [56], FastMNMF [57], LaplaceFDICA [58], and t-ILRMA [59]. The results are shown in Table 28(bottom).…”
Section: Case Study: a Common Officementioning
confidence: 99%
“…After extracting features to separate the source signals, we utilize methods such as STFT, CWT, WVD, and FrFT for separating and recovering the source signals from both the original mixed signals and the mixed signals with added noise [38], [39].This allows us to compare the significant role of time-frequency analysis in the process of source signal recovery. From Figures 19-22, it can be observed that STFT WVD exhibit relatively better recovery results, whereas CWT shows inferior performance primarily due to the impact of cross-terms, leading to significant deviations.…”
Section: ) Recovering Source Signalsmentioning
confidence: 99%
“…By considering the low-rank time-frequency structure of the source signal, IVA is further extended to an independent low-rank matrix analysis (ILRMA). ILRMA uses non-negative matrix factorization (NMF) to model the power spectrum of the source signals and achieves the best separation performance [21]. On the basis of ILRMA, Kohei Yatabe et al proposed harmonic vector analysis (HVA) to solve the problem of BSS of convoluted mixed speech signals [22].…”
Section: Introductionmentioning
confidence: 99%